Central Nervous System Tuberculosis in a Murine Model: Neurotropic Strains or a New Pathway of Infection? - Daniel Rembao-Bojórquez; Carlos Sánchez-Garibay; Citlaltepetl Salinas-Lara; Brenda Marquina-Castillo; Adriana Letechipía-Salcedo; Omar Jorge Castillón-Benavides; Sonia Galván-Arzate; Marcos Gómez-López; Luis Antonio Jiménez-Zamudio; Luis O. Soto-Rojas; Martha Lilia Tena-Suck; Porfirio Nava; et al. (Pathogens, 2023)
Tuberculosis (TB) of the central nervous system (CNS) is a lethal and incapacitating disease. Several studies have been performed to understand the mechanism of bacterial arrival to CNS, however, it remains unclear. Although the interaction of the host, the pathogen, and the environment trigger the course of the disease, in TB the characteristics of these factors seem to be more relevant in the genesis of the clinical features of each patient. We previously tested three mycobacterial clinical isolates with distinctive genotypes obtained from the cerebrospinal fluid of patients with meningeal TB and showed that these strains disseminated extensively to the brain after intratracheal inoculation and pulmonary infection in BALB/c mice. In this present study, BALB/c mice were infected through the intranasal route. One of these strains reaches the olfactory bulb at the early stage of the infection and infects the brain before the lungs, but the histological study of the nasal mucosa did not show any alteration. This observation suggests that some mycobacteria strains can arrive directly at the brain, apparently toward the olfactory nerve after infecting the nasal mucosa, and guides us to study in more detail during mycobacteria infection the nasal mucosa, the associated connective tissue, and nervous structures of the cribriform plate, which connect the nasal cavity with the olfactory bulb.